Brain-computer Interfaces and Art: Toward a Theoretical Framework. - Alfano, Veronica (International Journal of Humanities & Arts Computing: A Journal of Digital Humanities, 2019)
Art that incorporates brain-computer interface (or BCI) technology sheds fresh light on several aspects of aesthetic theory. Because it is radically interactive and can permit viewers or listeners to modify a work directly by means of their cerebral activity, such art illuminates the role of audience members in shaping that work's meaning; in this way, it literalizes reader-response theory and allows the public to engage even with opaque or alienating pieces. BCI-based art also reframes the significance of the artist's intentions, prompting a reconsideration of the truism that 'the author is dead', both by positing a collective form of authorship and by granting a creator access to her own unconscious impulses. Finally, via the notion that it may be possible to transfer unfiltered ideas between brains, BCI-inspired artworks provide a new perspective on art as mediation. Although artists have traditionally been praised for seeming to grant direct access to their emotions, one could argue that artistry happens in the act of concretizing and externalizing one's ideas – that is, in the mediated translation of thought rather than in thought itself. The essay concludes by discussing the implications of this theoretical framework for (among other fields) the digital humanities.